Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan, Reputasi Kantor Akuntan Publik (KAP) dan Komite Audit Terhadap Ketepatan Waktu Penyampaian Laporan Keuangan Pada Perusahaan Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia (BEI) - Devi Ayu Putri Sirait (Universitas Islam Negeri Sumatera Utara, 2021)
This study aims to examine and analyze the effect of profitability, leverage, firm size, reputation of public accounting firm and audit committee on timeliness of financial statement submission. This research was conducted at manufacturing industry sector of consumer goods sector in 2012-2016 at Indonesia Stock Exchange. Methods of research data using nonparticipant observation method, by analyzing the annual report and audit financial statements obtained. Data analysis method is logistic regression analysis, with hypothesis testing done by multivariate test. The result of the research shows that profitability and audit committee have positive effect on the timeliness of financial statement submission, while leverage, company size, reputation of public accountant office have no effect on the timeliness of financial reporting. With this research, it is expected to provide significant implications for the parties concerned in assessing and predicting the timeliness of financial statement submission.